Alasan Filipina Melakukan Kerja Sama Joint Coast Guard Committee (JCGC) Bersama Cina Tahun 2016 - Arima Rahayu, Ni Ketut Julianti; Widya Nugraha, A. A. Bagus Surya; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT This research aims to explain the reasons for the Philippines under Duterte's administration in establishing a Joint Coast Guard Committee (JCGC) with China in 2016. JCGC is maritime cooperation in the form of joint patrols in the South China Sea dispute area conducted by the Philippine coast guard and the China coast guard. The decision to establish cooperation with China is a new thing in Philippine foreign policy, given the relations between the two countries in the previous government, which was not good. The theoretical framework in this research used the concept of absolute gains in the view of neoliberalism. This research found that this cooperation could help the Philippines achieve its national interests in maintaining territorial integrity and can minimize the disputes between the Philippines and China in the South China Sea. Keywords: Philippine, China, JCGC, absolute gains